Application of POCCC Management Theories of Family Health Volunteers to Prevent Dengue Hemorrhagic Fever - จันทาคึมบง, ธนกร (Journal of Health Science of Thailand, 2021)
Dengue hemorrhagic fever (DHF) is an endemic disease in Thailand. In Kantharawichai district, Mahasarakham province, the incidence rates are higher than the criteria of the Ministry of Public Health. Disease management has been unclear, and a concrete health network has not been run. This research employed the management theory of Henri Foyol to study the applied POCCC for preventing the DHF among family health volunteer in Kantharawichai district. This quasi-experimental research studied in 128 families of health volunteers. The samples were selected by simple random sampling method into an experimental group and a comparison group, 64 persons per group. Data were collected from February to July 2018. The experimental group received the application activities of the POCCC for the prevention of DHF, including Planning, Organizing, Commanding, Coordinating, and Controlling. Data collection tool was a questionnaire and the mosquito larvae survey of Department of Disease Control. Data were analyzed using descriptive statistics such as percentage, mean, standard deviation and inferential statistics including paired t-test, independent t-test. The results showed that after the experiment, the experimental group had scores of knowledge, participation, and disease prevention and control higher than before the experiment; and higher those of the comparison group (p<0.05). Comparing the index prevalence of Aedes aegypti larvae (HI, CI, BI), after repeated trials within 1 month and 3 months in the experimental group, they were lower than before the experiment and lower than the comparison group. In summary, the application of this management theory made the family health volunteers increased their participation. The systematically management could reduce the morbidity rate of dengue hemorrhagic fever in the community. The folksong poetry was created to continuously promote health to people in the community.